Temperature Effects on Conductivities and Association Constants of Lithium and Tetra-Ethylammonium Salts in Six Aprotic Solvents of Medium to High Permittivities from - 30 ºC to + 10 ºC - Viana,César A.N. (2004)
A few non-aqueous dipolar aprotic solvents of medium to high permittivities, low viscosities and large temperature intervals between freezing and boiling points have been used to prepare electrolyte solutions applicable to primary and rechargeable high energy batteries. Lithium perchlorate is a salt often chosen to obtain those systems. In this work low temperature effects on conductivities and association constants of LiClO4 and Et4NBr in six different solvents have been analyzed, using the tetraethylammonium bromide salt for comparative reasons. The temperature interval was -30 ºC to 10 ºC. A few thermodynamic functions resulting from K A, T variations were determined being the results discussed on this basis. The accuracy and precision of results are high; whenever possible they are compared with others previously published.